Industrial Internet of Things – An Overview - Sailaja, C. (Journal of ISMAC, 2022)
Internet of Things (IoT) is a network of intelligent objects (smart sensors) that are connected and accessible to the Internet through devices such as routers to exchange data. Many useful applications can be developed using IoT. IoT has brought a change in such a way that everything around us can be turned into smart devices e.g., smart cars, smart homes, smart parking, smart cities etc., thereby connecting human, machine & things seamlessly. The advent of cheaper processing power, communication cost and some marketing have created the IoT of today. When the principles of IoT are applied to Industries, it is termed as Industrial IoT. Smart sensors and Industrial Internet of Things (IIoT) are modern tools which drive Industry 4.0. The use of smart sensors and IIoT have a positive impact in enhancing the quality & value of products and improve efficiency. The combination of smart sensors with its processing & networking capabilities help in transferring the process data to the centralized database for further analysis. Thus, digitalization has helped industry to reimage the business with the transformation brought about by IIoT. This paper discusses some of the applications of IIoT such as Remote Monitoring & Service, AI & ML based predictive analysis and Closed loop Digital twin using IoT sensors.